Electronegativity of atoms in molecules - Racioppi, Stefano; Rahm, Martin (Chalmers University of Technology, 2021)
The purpose of this study is to investigate electronegativity and charges of atoms in molecules. These properties have been obtained from topological analyses of the real space representation of the electron energy density. This dataset includes cartesian coordinates as output from molecular calculations done using ADF, at the LC-BLYP/ATZ2P level of theory. A complete set of outputs files is provided for one example molecule, ammonia, NH3. The NH3 example set also contains files (of the type .cube) used for the topological analysis.

Målet med denna studie är att undersöka elektronegativitet och laddning av atomer inuti molekyler. Dessa egenskaper har beräknats genom topologisk analys av den tredimensionella representationen av elektronernas energitäthet. Denna samling data innefattar kartesiska koordinater från molekylära beräkningar utförda med ADF och vågfunktioner av kvalitén LC-BLYP/ATZ2P. En fullständig upplaga av beräkningsresultatsfiler är bifogat för ett exempel, ammonia, NH3. NH3-exemplet innehåller även filer (av typen .cube) som använts för den topologiska analysen.
Elektronegativitet för atomer i molekyler
Keywords: Small molecules; Small molecules; electronegativity; electronegativity; ADF; ADF; Theoretical Chemistry; Teoretisk kemi